A method for preparing silicon-carbon composite negative electrode material for power lithium-ion battery
By coating nanosilicon particles with polyimide and combining them with graphite materials, a silicon-carbon composite negative electrode material with excellent electrochemical performance was prepared, which solved the problems of insufficient performance of the negative electrode material of lithium-ion batteries and the expansion of silicon volume, and achieved efficient and economical material preparation.
Patent Information
- Application Number
- CN201510217448.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2015-04-30
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2035-04-30
AI Technical Summary
The negative electrode material of existing lithium-ion batteries is mainly graphite, which has a lower theoretical energy and poor charging and discharge performance at high magnification. Silicon has serious volume expansion problems as a substitute material, which limits its industrial application.
The nanosilicon particles are coated with polyimide, and spray-drying granulation and high-temperature calcination are used to form a conductive carbon layer to cover the silicon nanoparticles, and silicon-carbon composite anode material is prepared in combination with graphite materials.
It effectively suppresses the volume effect of silicon particles during charging and discharging, avoids unnecessary side reactions between silicon and electrolyte, improves the circulation and rate performance of the material, and reduces the preparation cost.
Smart Images

Figure CN106207142B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of power lithium-ion battery production, and in particular to a method for preparing a silicon-carbon composite negative electrode material for a power lithium-ion battery. Background Art
[0002] With the rapid development and widespread application of various 3C electronic products and electric vehicles, the demand for lithium-ion batteries with high energy density, good rate performance and good cycle performance has become more urgent. At present, the negative electrode material of commercial lithium-ion batteries is mainly graphite. Due to its low theoretical specific energy (372mAh / g) and poor high-rate charge and discharge performance, it is a stumbling block to the further development of lithium-ion batteries. Compared with traditional graphite that forms LiC6 intercalation compounds after being embedded in lithium, silicon, as a negative electrode material, usually alloys with lithium to form Li22Si5 intermetallic compounds, with a theoretical specific capacity of up to 3572mAh / g. However, when this compound is formed, the structure of the component crystals will be reconstructed, accompanied by a large volume expansion (up to 300%). At the same time, it will also cause uneven volume changes in the boundary area between the two phases in the crystal material, causing the silicon particles to break or pulverize, resulting in loss of contact with the electrode, and even causing the collapse of the negative electrode. The lithium embedded in the silicon cannot be removed in the subsequent process, forming the so-called "dead lithium". Due to the serious volume effect of silicon itself, the industrialization of silicon negative electrode materials is seriously restricted.
[0003] In order to avoid this unfavorable situation, the volume expansion of pure silicon is improved mainly by nano-sizing silicon, alloying silicon with metals, and compounding silicon with active or inactive materials, among which the compounding of silicon with active carbon has great application prospects. CN102683649A uses resorcinol and formaldehyde to form a carbon aerogel coating layer with a pore structure on the surface of nano silicon powder and ultrafine graphite. Although the surface structure and cycle performance of silicon-carbon materials are improved, the material has a large specific surface area and low initial efficiency, which limits its application in lithium batteries. CN102769139A uses natural granular graphite as raw material, concentrated sulfuric acid as intercalation agent, potassium permanganate as oxidant, and then performs expansion treatment at high temperature to prepare micro-expanded graphite, and mixes nano silicon with the graphite, followed by carbon source coating and heat treatment to obtain silicon-carbon composite negative electrode material. This method prepares micro-expanded graphite in a strong acidic environment, and the reaction requirements are relatively high. CN101244814A mixes asphalt solution, nano silicon powder and granular natural graphite to carbonize and prepare silicon-carbon negative electrode material. This method is difficult to evenly disperse the nano silicon powder, and the first efficiency of the prepared material is low.
[0004] Therefore, developing a lithium-ion battery silicon-carbon composite negative electrode material with excellent electrochemical performance and simple preparation method is a difficulty in the technical field. Summary of the invention
[0005] The technical problem to be solved by the present application is to provide a method for preparing a silicon-carbon composite negative electrode material for a power lithium-ion battery in view of the deficiencies in the prior art.
[0006] The technical problem to be solved by this application is solved by the following technical solutions:
[0007] A method for preparing a silicon-carbon composite negative electrode material for a power lithium-ion battery, comprising:
[0008] preparing polyimide-coated nano-silicon particle slurry;
[0009] The slurry is spray-dried and granulated to obtain polyimide-coated nano-silicon particle powder;
[0010] The polyimide-coated nano-silicon particle powder is placed in a reactor for high-temperature calcination, and then crushed without destroying the coating structure and granulated;
[0011] The crushed powder is mixed with graphite material powder to prepare a silicon-carbon composite negative electrode material.
[0012] In the above method, the graphite powder has a particle size of 5 to 25 μm and a carbon content of 80 to 99.9%.
[0013] In the above method, the preparation of polyimide-coated nano-silicon particle slurry specifically includes:
[0014] Adding nano silicon particle powder and silane coupling agent into a high boiling point polar aprotic solvent and stirring for a predetermined time;
[0015] Add aromatic diamine and stir until the aromatic diamine is completely dissolved;
[0016] Under the condition of ice water bath and stirring, adding aromatic dianhydride into the reaction system several times, stirring to obtain composite glue solution;
[0017] The composite glue solution is degraded in a hot water bath, filtered, and chemically imidized with acetic anhydride and pyridine.
[0018] In the above method, the high-boiling-point polar aprotic solvent includes N,N'-dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide or cyclopentane sulfone; the aromatic diamine includes p-phenylenediamine, m-phenylenediamine, diphenylmethanediamine, 4,4'-diaminodiphenyl ether, diaminodiphenyl sulfone or 4,4'-biphenylenediamine; the aromatic dianhydride includes diphenyl ether tetracarboxylic dianhydride, pyromellitic dianhydride, keto anhydride or hexafluoro dianhydride.
[0019] In the above method, the mass ratio of the nano silicon particle powder to the silane coupling agent is 1:(0.03-0.07); the mass ratio of the nano silicon particle powder to the high boiling point polar aprotic solvent is 1:(0.03-0.6); the mass ratio of the nano silicon particle powder to the aromatic diamine is 1:(2-60); the mass ratio of the aromatic diamine to the pyromellitic dianhydride is 1:1; the mass ratio of the aromatic dianhydride to the acetic anhydride is 1:1; the mass ratio of the acetic anhydride to the pyridine is 1:1.
[0020] In the above method, the silane coupling agent includes one or a combination of γ-aminopropyltriethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane, octyltriethoxysilane, dimethyldimethoxysilane, methyltributylidene oxime silane and isocyanatepropyltriethoxysilane.
[0021] In the above method, the high-temperature calcining of the polyimide-coated nano-silicon particles specifically includes:
[0022] The polyimide-coated nano-silicon particles are placed in a reactor for calcination at a heating rate of 1°C to 5°C / min to a temperature of 600 to 900°C, calcined for 1 to 10 hours, and naturally cooled to room temperature.
[0023] In the above method, the reactor includes a rotary kiln, a roller kiln, a pusher kiln or a tubular furnace; a protective gas is filled in during the heating, calcining and cooling processes, and the flow rate of the protective gas is 0.5 to 5 L / min.
[0024] In the above method, when the slurry is spray-dried and granulated, the feed rate is 5Kg / h to 15Kg / h, the air inlet temperature is 200 to 300°C, the air outlet temperature is 90 to 150°C, and the spray frequency is 250 to 350Hz.
[0025] In the above method, the mass ratio of the polyimide-coated nano-silicon particle powder to the silicon-carbon composite negative electrode material is (7-20):100.
[0026] Due to the adoption of the above technical solution, the beneficial effects of this application are:
[0027] In a specific embodiment of the present application, since the conductive carbon layer produced by the pyrolysis of the polyimide polymer is uniformly covered on the surface of the silicon nanoparticles, it not only effectively suppresses the volume effect of the silicon particles during the charging and discharging process of the battery, but also avoids unnecessary side reactions between silicon and the electrolyte. The nano-silicon particle dispersion containing the polyimide polymer not only effectively suppresses the agglomeration of the silicon nanoparticles in the dispersion, but also can be used as a binder in the next spray drying process. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 A flowchart of a method of the present application in one embodiment;
[0029] Figure 2 This is a scanning electron microscope image (SEM) of the silicon-carbon negative electrode material for a power lithium-ion battery according to Example 1 of the present application;
[0030] Figure 3 This is a graph showing the first 0.5C charge and discharge performance of the silicon-carbon negative electrode material for a power lithium-ion battery according to Example 1 of the present application;
[0031] Figure 4 The silicon-carbon negative electrode material of the power lithium-ion battery of Example 1 of the present application is charged at the same current density (0.5C), different current densities (0.2C, 0.5C, 1C, 2C, 4C), and the discharge performance curve under the voltage range of 2.75-4.2V;
[0032] Figure 5 This is the 0.5C charge-discharge cycle performance curve of the power lithium-ion battery silicon-carbon negative electrode material prepared in Example 1 of the present application. DETAILED DESCRIPTION
[0033] The present application is further described in detail below through specific implementation methods in conjunction with the accompanying drawings.
[0034] like Figure 1 As shown, the method for preparing the silicon-carbon composite negative electrode material of the power lithium-ion battery of the present application, one embodiment of which comprises the following steps:
[0035] Step 102: Prepare polyimide-coated nano-silicon particle slurry.
[0036] Step 104: spray-dry and granulate the slurry to obtain polyimide-coated nano-silicon particle powder.
[0037] When the slurry is spray-dried and granulated, the feed rate is 5Kg / h to 15Kg / h, the air inlet temperature is 200 to 300°C, the air outlet temperature is 90 to 150°C, and the spray frequency is 250 to 350Hz. Spray drying can be performed in a spray dryer or a spray drying equipment.
[0038] Step 106: placing the polyimide coated nano silicon particle powder in a reactor for high temperature calcination, and then crushing and granulating the powder without destroying the coating structure.
[0039] The polyimide-coated nano-silicon particles are placed in a reactor for calcination, with a heating rate of 1°C to 5°C / min to a temperature of 600 to 900°C, calcined for 1 to 10 hours, and naturally cooled to room temperature. The reactor includes a rotary kiln, a roller kiln, a pusher kiln or a tube furnace; a protective gas is filled in during the heating, calcination and cooling process, and the flow rate of the protective gas is 0.5 to 5L / min.
[0040] The pulverizing process can use a turbo pulverizer, an air vortex micronizer, a super cyclone vortex mill, an air separation pulverizer or a double-roll pulverizer.
[0041] Step 108: Mix the crushed powder with graphite material powder to obtain a silicon-carbon composite negative electrode material. The graphite material may include one or more of natural graphite, artificial graphite, composite graphite, soft carbon, hard carbon and mesophase carbon microspheres.
[0042] The particle size after crushing is 5-25um, the particle size of graphite powder is 5-25um, and the carbon content is 80-99.9%. The mass ratio of polyimide coated nano silicon particle powder to silicon carbon composite negative electrode material is (7-20):100.
[0043] The equipment used for the mixing process is a V-type mixer, a trough mixer, a drum mixer, a conical double-screw mixer or a double cone mixer.
[0044] Wherein, step 102 specifically includes the following steps:
[0045] Step 1022: Add nano silicon particle powder and silane coupling agent into a polar aprotic solvent with a high boiling point, and stir for a predetermined time.
[0046] The silane coupling agent includes one or a combination of γ-aminopropyl triethoxysilane, γ-(2,3-epoxypropyloxy)propyl trimethoxysilane, γ-(methacryloyloxy)propyl trimethoxysilane, octyl triethoxysilane, dimethyl dimethoxysilane, methyl tributanooxime silane and isocyanate propyl triethoxysilane. The high boiling point polar aprotic solvent includes N,N'-dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide or cyclopentane. The mass ratio of nano silicon particle powder to silane coupling agent is 1: (0.03-0.07); the mass ratio of nano silicon particle powder to high boiling point polar aprotic solvent is 1: (0.03-0.6).
[0047] Step 1024: Add aromatic diamine and stir until the aromatic diamine is completely dissolved;
[0048] The aromatic diamine includes p-phenylenediamine, m-phenylenediamine, diphenylmethanediamine, 4,4'-diaminodiphenyl ether, diaminodiphenyl sulfone or 4,4'-biphenylenediamine. The mass ratio of the nano silicon particle powder to the aromatic diamine is 1:(2-60);
[0049] Step 1026: adding aromatic dianhydride to the reaction system in multiple portions under ice-water bath and stirring, and stirring to obtain a composite adhesive solution;
[0050] The mass ratio of aromatic diamine to aromatic dianhydride is 1:1;
[0051] The aromatic dianhydride includes diphenyl ether tetracarboxylic dianhydride, pyromellitic dianhydride, keto anhydride or hexafluoro dianhydride.
[0052] Step 1028: Degrade the composite glue in a hot water bath, filter it, and then chemically imidize it with acetic anhydride and pyridine.
[0053] The mass ratio of aromatic dianhydride to acetic anhydride is 1:1; the mass ratio of acetic anhydride to pyridine is 1:1.
[0054] In one embodiment, nano silicon particle powder and silane coupling agent can be added to N,N'-dimethylacetamide under the condition of ultrasonic power of 150w-250w, ultrasonic stirring is performed for 12h-24h, 4,4'-diaminodiphenyl ether is added to the reaction system, and stirred until 4,4'-diaminodiphenyl ether is completely dissolved, and pyromellitic dianhydride is added to the reaction system in 4-8 times under the condition of ice water bath and stirring speed of 1000r / min-2000r / min, and stirred for 12h-24h to obtain composite glue, and then the composite glue is degraded in a hot water bath at a temperature of 30°C-70°C for 30min-60min, and filtered to remove gas and impurities, and finally chemically imidized with acetic anhydride and pyridine to obtain nano silicon particle / polyimide slurry.
[0055] The power lithium-ion battery silicon-carbon composite negative electrode material prepared by the method of the present application first has good cycle performance, and because of its high specific capacity and rate performance, it has good application prospects in the fields of 3C and power lithium-ion batteries; secondly, the preparation cost is low, there are no harsh conditions, the process is simple and controllable, and it is easy to industrialize; finally, by adjusting the mass ratio of silicon powder, polymer and graphite, silicon-carbon composite negative electrode materials of different capacities can be easily prepared.
[0056] Embodiment 1:
[0057] 1. Preparation of polyimide-coated nano-silicon particle slurry: Under the condition of ultrasonic power of 150w, 1kg of nano-silicon particle powder and 30g of silane coupling agent were added to 600g of N,N'-dimethylacetamide, and ultrasonic stirring was performed for 12h. Then 2kg of 4,4'-diaminodiphenyl ether was added to the reaction system, and stirred until 4,4'-diaminodiphenyl ether was completely dissolved. Under the condition of ice water bath and stirring speed of 1000r / min, 2.178kg of pyromellitic dianhydride was added to the reaction system in 4 times, and stirred for 12h to obtain a composite glue solution. Then, the composite glue solution was degraded in a hot water bath at a temperature of 30°C for 30min, and filtered to remove gas and impurities. Finally, 1kg of acetic anhydride and 1kg of pyridine were used for chemical imidization to obtain nano-silicon particle / polyimide slurry;
[0058] 2. Preparation of polyimide-coated nano-silicon particles: The slurry was spray-dried and granulated, with a feed rate of 5 Kg / h, an air inlet temperature of 200° C., an air outlet temperature of 90° C., and a spray frequency of 250 Hz.
[0059] 3. High-temperature calcination: The dried powder is calcined in a reactor at a heating rate of 3°C / min to a temperature of 600°C for 1 hour. After the calcination, the furnace is naturally cooled to room temperature.
[0060] 4. Crushing: The coated material prepared above is crushed and granulated according to the existing technology without destroying its coating structure, and the particle size distribution after crushing is 5 to 10 um.
[0061] 5. Blending with graphite powder: According to the capacity requirements of lithium-ion batteries, the crushed powder is mixed with a graphite material with an average particle size of 10-15um and a carbon content of 80%, wherein the silicon-carbon composite powder accounts for 7% of the mass of the lithium-ion battery silicon-carbon composite negative electrode material to obtain a lithium-ion battery silicon-carbon composite negative electrode material.
[0062] Figure 2 This is a scanning electron microscope image (SEM) of the silicon-carbon negative electrode material for a power lithium-ion battery of Example 1; Figure 3 The first 0.5C charge-discharge performance curve of the power lithium-ion battery silicon-carbon negative electrode material of Example 1; Figure 4 The discharge performance curves of the power lithium-ion battery silicon-carbon negative electrode material of Example 1 under the same current density (0.5C), different current densities (0.2C, 0.5C, 1C, 2C, 4C), and a voltage range of 2.75-4.2V; Figure 5 The 0.5C charge-discharge cycle performance curve of the power lithium-ion battery silicon-carbon negative electrode material prepared in Example 1.
[0063] Embodiment 2:
[0064] 1. Preparation of polyimide-coated nano-silicon particle slurry: Under the condition of ultrasonic power of 180w, 1kg of nano-silicon particle powder and 40g of silane coupling agent were added to 700g of N,N'-dimethylacetamide, and ultrasonic stirring was performed for 14h. Then 3kg of 4,4'-diaminodiphenyl ether was added to the reaction system, and stirred until 4,4'-diaminodiphenyl ether was completely dissolved. Under the condition of ice water bath and stirring speed of 1200r / min, 3.267kg of pyromellitic anhydride was added to the reaction system in 4 times, and stirred for 14h to obtain a composite glue solution. Then, the composite glue solution was degraded in a hot water bath at a temperature of 30°C for 30min, and filtered to remove gas and impurities. Finally, 1.5kg of acetic anhydride and 1.5kg of pyridine were used for chemical imidization to obtain nano-silicon particle / polyimide slurry;
[0065] 2. Preparation of nano silicon particles / polyimide particles: The slurry was spray dried and granulated, the feed rate was 6 Kg / h, the air inlet temperature was 220° C., the air outlet temperature was 100° C., and the spray frequency was 270 Hz.
[0066] 3. High-temperature calcination: The dried powder is calcined in a reactor at a heating rate of 3°C / min to a temperature of 650°C for 1.5 hours. After the calcination, the furnace is naturally cooled to room temperature.
[0067] 4. Crushing: The coated material prepared above is crushed and granulated according to the existing technology without destroying its coating structure, and the particle size distribution after crushing is 6 to 12 um.
[0068] 5. Blending with graphite powder: According to the capacity requirements of lithium-ion batteries, the crushed powder is mixed with a graphite material with an average particle size of 5 to 10 um and a carbon content of 82.5%, wherein the silicon-carbon composite powder accounts for 8% of the mass of the lithium-ion battery silicon-carbon composite negative electrode material to obtain a lithium-ion battery silicon-carbon composite negative electrode material.
[0069] Embodiment three:
[0070] 1. Preparation of polyimide-coated nano-silicon particle slurry: Under the condition of ultrasonic power of 200w, 1kg of nano-silicon particle powder and 50g of silane coupling agent were added to 800g of N,N'-dimethylacetamide, and ultrasonic stirring was performed for 15h. Then 4Kg of 4,4'-diaminodiphenyl ether was added to the reaction system and stirred until 4,4'-diaminodiphenyl ether was completely dissolved. Under the condition of ice water bath and stirring speed of 1350r / min, 4.356Kg of pyromellitic dianhydride was added to the reaction system in 5 times, stirred for 16h, and a composite glue solution was obtained. Then, the composite glue solution was degraded in a hot water bath at a temperature of 40°C for 40min, and filtered to remove gas and impurities. Finally, 2Kg of acetic anhydride and 2Kg of pyridine were used for chemical imidization to obtain nano-silicon particle / polyimide slurry;
[0071] 2. Preparation of polyimide-coated nano-silicon particles: The slurry was spray-dried and granulated, the feed rate was 6 Kg / h, the air inlet temperature was 240° C., the air outlet temperature was 110° C., and the spray frequency was 270 Hz.
[0072] 3. High-temperature calcination: The dried powder is calcined in a reactor at a heating rate of 3°C / min to a temperature of 750°C for 3 hours. After the calcination, the furnace is naturally cooled to room temperature.
[0073] 4. Crushing: The coated material prepared above is crushed and granulated according to the existing technology without destroying its coating structure, and the particle size distribution after crushing is 15 to 25 μm.
[0074] 5. Blending with graphite powder: According to the capacity requirements of lithium-ion batteries, the crushed powder is mixed with a graphite material with an average particle size of 10-20um and a carbon content of 85%, wherein the silicon-carbon composite powder accounts for 9% of the mass of the lithium-ion battery silicon-carbon composite negative electrode material to obtain a lithium-ion battery silicon-carbon composite negative electrode material.
[0075] Embodiment 4:
[0076] 1. Preparation of polyimide-coated nano-silicon particle slurry: Under the condition of ultrasonic power of 200w, 1kg of nano-silicon particle powder and 50g of silane coupling agent were added to 900g of N,N'-dimethylacetamide, and ultrasonic stirring was performed for 16h. Then 6kg of 4,4'-diaminodiphenyl ether was added to the reaction system, and stirred until 4,4'-diaminodiphenyl ether was completely dissolved. Under the condition of ice water bath and stirring speed of 1600r / min, 6.534kg of pyromellitic anhydride was added to the reaction system in 6 times, and stirred for 16h to obtain a composite glue solution. Then, the composite glue solution was degraded in a hot water bath at a temperature of 50°C for 50min, and filtered to remove gas and impurities. Finally, 3kg of acetic anhydride and 3kg of pyridine were used for chemical imidization to obtain nano-silicon particle / polyimide slurry;
[0077] 2. Preparation of polyimide-coated nano-silicon particles: The slurry was spray-dried and granulated, with a feed rate of 10 Kg / h, an air inlet temperature of 250° C., an air outlet temperature of 120° C., and a spray frequency of 300 Hz.
[0078] 3. High-temperature calcination: The dried powder is calcined in a reactor at a heating rate of 3°C / min to a temperature of 800°C for 5 hours. After the calcination, the furnace is naturally cooled to room temperature.
[0079] 4. Crushing: The coated material prepared above is crushed and granulated according to the existing technology without destroying its coating structure, and the particle size distribution after crushing is 7 to 22 um.
[0080] 5. Blending with graphite powder: According to the capacity requirements of lithium-ion batteries, the crushed powder is mixed with a graphite material with an average particle size of 5 to 18 um and a carbon content of 90%, wherein the silicon-carbon composite powder accounts for 10% of the mass of the lithium-ion battery silicon-carbon composite negative electrode material to obtain a lithium-ion battery silicon-carbon composite negative electrode material.
[0081] Embodiment five:
[0082] 1. Preparation of polyimide-coated nano-silicon particle slurry: Under the condition of ultrasonic power of 220w, 1Kg of nano-silicon particle powder and 50g of silane coupling agent were added to 1Kg of N, N'-dimethylacetamide, and ultrasonic stirring was performed for 18h. Then 8Kg of 4, 4'-diaminodiphenyl ether was added to the reaction system, and stirred until 4, 4'-diaminodiphenyl ether was completely dissolved. Under the condition of ice water bath and stirring speed of 1600r / min, 8.712Kg of pyromellitic anhydride was added to the reaction system in 6 times, and stirred for 18h to obtain a composite glue solution. Then, the composite glue solution was degraded in a hot water bath at a temperature of 60°C for 50min, and filtered to remove gas and impurities. Finally, 4Kg of acetic anhydride and 4Kg of pyridine were used for chemical imidization to obtain nano-silicon particle / polyimide slurry;
[0083] 2. Preparation of polyimide-coated nano-silicon particles: The slurry was spray-dried and granulated, with a feed rate of 12 Kg / h, an air inlet temperature of 270° C., an air outlet temperature of 125° C., and a spray frequency of 300 Hz.
[0084] 3. High-temperature calcination: The dried powder is calcined in a reactor at a heating rate of 3°C / min to a temperature of 800°C for 6 hours. After the calcination, the furnace is naturally cooled to room temperature.
[0085] 4. Crushing: The coated material prepared above is crushed and granulated according to the prior art without destroying its coating structure, and the particle size distribution after crushing is 12 to 18 um.
[0086] 5. Blending with graphite powder: According to the capacity requirements of lithium-ion batteries, the crushed powder is mixed with a graphite material with an average particle size of 10-22um and a carbon content of 92%, wherein the silicon-carbon composite powder accounts for 15% of the mass of the silicon-carbon composite negative electrode material of the lithium-ion battery, and a lithium-ion battery silicon-carbon composite negative electrode material is obtained.
[0087] Embodiment six:
[0088] 1. Preparation of polyimide-coated nano-silicon particle slurry: Under the condition of ultrasonic power of 240w, 1Kg of nano-silicon particle powder and 60g of silane coupling agent were added to 1.2Kg of N,N'-dimethylacetamide, and ultrasonic stirring was performed for 22h. Then 10Kg of 4,4'-diaminodiphenyl ether was added to the reaction system, and stirred until 4,4'-diaminodiphenyl ether was completely dissolved. Under the condition of ice water bath and stirring speed of 1800r / min, 10.89Kg of pyromellitic anhydride was added to the reaction system in 8 times, and stirred for 22h to obtain a composite glue solution. Then, the composite glue solution was degraded in a hot water bath at a temperature of 70°C for 60min, and filtered to remove gas and impurities. Finally, 5Kg of acetic anhydride and 5Kg of pyridine were used for chemical imidization to obtain nano-silicon particle / polyimide slurry;
[0089] 2. Preparation of polyimide-coated nano-silicon particles: The slurry was spray-dried and granulated, the feed rate was 14 Kg / h, the air inlet temperature was 280° C., the air outlet temperature was 140° C., and the spray frequency was 320 Hz.
[0090] 3. High-temperature calcination: The dried powder is calcined in a reactor at a heating rate of 3°C / min to a temperature of 900°C for 8 hours. After the calcination, the furnace is naturally cooled to room temperature.
[0091] 4. Crushing: The coated material prepared above is crushed and granulated according to the existing technology without destroying its coating structure, and the particle size distribution after crushing is 15 to 25 μm.
[0092] 5. Blending with graphite powder: According to the capacity requirements of lithium-ion batteries, the crushed powder is mixed with a graphite material with an average particle size of 10-20um and a carbon content of 95%, wherein the silicon-carbon composite powder accounts for 15% of the mass of the silicon-carbon composite negative electrode material of the lithium-ion battery, and a lithium-ion battery silicon-carbon composite negative electrode material is obtained.
[0093] Performance test of silicon-carbon composite negative electrode materials for lithium-ion batteries:
[0094] 1. Assembly and testing of half-cells: The negative electrode materials of lithium-ion batteries prepared in Examples 1 to 6 were respectively mixed with the conductive agent acetylene black, the binder CMC (sodium hydroxymethyl cellulose) and SBR (styrene-butadiene rubber) in a mass ratio of 8:1:1, and mixed with water as a solvent and a particle grinder, and then coated on a copper foil to prepare an electrode. Before assembling the battery, cut it into small pole pieces of 1cm×1cm and vacuum dry it at 120°C for 12h. Assemble CR2025 batteries in a glove box (M Braun), with pure Li sheets as the negative electrode, Celgard 2300 as the diaphragm, and EC:DMC (1:1 volume ratio, 1mol / L LiPF6, Samsung) as the electrolyte. Use Land to perform charge and discharge tests on the battery;
[0095] 2. The negative electrode materials prepared in Examples 1 to 6 were assembled into half-cells and charged and discharged at a current density of 0.5C at 25°C, with a charge and discharge voltage of 0.001 to 1.5V.
[0096] Table 1 Discharge cycle test data of the power lithium-ion battery silicon-carbon composite negative electrode material prepared in Example
[0097]
[0098] 3. Assembly and testing of the full battery: The power lithium-ion battery silicon-carbon composite negative electrode material prepared in Example 1 is used as the negative electrode active material of the lithium-ion battery, the conductive agent acetylene black, styrene-butadiene rubber SBR as the binder, and carboxymethyl cellulose CMC as the thickener to obtain the electrode material; the three are mixed in a mass ratio of active material: CMC: SBR = 96.5:1.5:1.5:2. Add an appropriate amount of deionized water, mix it into a paste with a slurry mixer, and then use a coating machine to apply the coating on the copper foil, and vacuum dry it to make the negative electrode of the lithium-ion full battery. Lithium cobalt oxide LiCoO2, lithium nickel oxide LiNiO2 or spinel lithium manganese oxide LiMn2O4 are used as positive electrode materials; 1MLiPF6 / EC+DMC+EMC is used as the electrolyte; Celgard2300 type PE / PP / PE composite film is used as the diaphragm; the full battery is assembled using the production process of conventional 18650 single cells, and the Wuhan Jinnuo Land CT2001A charge and discharge test cabinet is used.
[0099] The above contents are further detailed descriptions of the present application in combination with specific implementation methods, and it cannot be determined that the specific implementation of the present application is limited to these descriptions. For ordinary technicians in the technical field to which the present application belongs, several simple deductions or substitutions can be made without departing from the concept of the present application.
Claims
1. A method for preparing a silicon-carbon composite negative electrode material for a power lithium-ion battery, characterized in that: include: preparing polyimide-coated nano-silicon particle slurry; The slurry is spray-dried and granulated to obtain polyimide-coated nano-silicon particle powder; The polyimide-coated nano-silicon particle powder is placed in a reactor for high-temperature calcination, and then crushed without destroying the coating structure and granulated; The crushed powder is mixed with graphite material powder to prepare a silicon-carbon composite negative electrode material.
2. The method for preparing a silicon-carbon composite negative electrode material for a power lithium-ion battery according to claim 1, characterized in that: The graphite powder has a particle size of 5 to 25 μm and a carbon content of 80 to 99.9%.
3. The method for preparing a silicon-carbon composite negative electrode material for a power lithium-ion battery according to claim 1, characterized in that: The preparation of the polyimide-coated nano-silicon particle slurry specifically comprises: Adding nano silicon particle powder and silane coupling agent to a high boiling point polar aprotic solvent and stirring for a predetermined time; the high boiling point polar aprotic solvent includes N,N'-dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide or sulfolane; Add aromatic diamine and stir until the aromatic diamine is completely dissolved; Under the condition of ice water bath and stirring, adding aromatic dianhydride into the reaction system several times, stirring to obtain composite glue solution; The composite glue solution is degraded in a hot water bath, filtered, and chemically imidized with acetic anhydride and pyridine.
4. The method for preparing a silicon-carbon composite negative electrode material for a power lithium-ion battery according to claim 3, characterized in that: The aromatic diamines include p-phenylenediamine, m-phenylenediamine, diphenylmethanediamine, 4,4'-diaminodiphenyl ether, diaminodiphenyl sulfone or 4,4'-biphenylenediamine; the aromatic dianhydrides include diphenyl ether tetracarboxylic dianhydride, pyromellitic dianhydride, ketoanhydride or hexafluorodianhydride.
5. The method for preparing a silicon-carbon composite negative electrode material for a power lithium-ion battery according to claim 4, characterized in that: The mass ratio of the nano silicon particle powder to the silane coupling agent is 1:(0.03-0.07); the mass ratio of the nano silicon particle powder to the high boiling point polar aprotic solvent is 1:(0.03-0.6); the mass ratio of the nano silicon particle powder to the aromatic diamine is 1:(2-60); the mass ratio of the aromatic diamine to the pyromellitic dianhydride is 1:1; the mass ratio of the aromatic dianhydride to the acetic anhydride is 1:1; the mass ratio of the acetic anhydride to the pyridine is 1:
1.
6. The method for preparing a silicon-carbon composite negative electrode material for a power lithium-ion battery according to claim 3, characterized in that: The silane coupling agent includes one or a combination of γ-aminopropyltriethoxysilane, γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane, octyltriethoxysilane, dimethyldimethoxysilane, methyltributylidene oxime silane and isocyanatepropyltriethoxysilane.
7. The method for preparing a silicon-carbon composite negative electrode material for a power lithium-ion battery according to claim 1, characterized in that: The polyimide-coated nano-silicon particles are subjected to high-temperature calcination, specifically comprising: The polyimide-coated nano-silicon particles are placed in a reactor for calcination at a heating rate of 1°C to 5°C / min to a temperature of 600 to 900°C, calcined for 1 to 10 hours, and naturally cooled to room temperature.
8. The method for preparing a silicon-carbon composite negative electrode material for a power lithium-ion battery according to claim 7, characterized in that: The reactor comprises a rotary kiln, a roller kiln, a pusher kiln or a tubular furnace; a protective gas is filled in during the heating, calcining and cooling processes, and the flow rate of the protective gas is 0.5 to 5 L / min.
9. The method for preparing a silicon-carbon composite negative electrode material for a power lithium-ion battery according to claim 2, characterized in that: When the slurry is spray-dried and granulated, the feed rate is 5Kg / h to 15Kg / h, the air inlet temperature is 200 to 300°C, the air outlet temperature is 90 to 150°C, and the spray frequency is 250 to 350Hz.
10. The method for preparing a silicon-carbon composite negative electrode material for a power lithium-ion battery according to claim 1, characterized in that: The mass ratio of the polyimide-coated nano-silicon particle powder to the silicon-carbon composite negative electrode material is (7-20):100.
Citation Information
Patent Citations
Method for producing lithium cell silicon carbon negative pole material and produced silicon carbon negative pole material
CN101244814A
Method for preparing lithium ion battery carbon silicon anode material
CN102683649A
Preparation method of high power capacity lithium ion battery cathode material
CN102769139A
Silicon-carbon composite cathode material of lithium ion battery and preparation thereof
CN101339987A
Method for preparing silicon carbide alloy negative electrode material for lithium ion battery
CN102376944A